Burnout experiences among nurses in Oman: A qualitative study - Al Busaidi, Ahmed; Harthy, Fatima; Al Maawali, Salim; Al Zajali, Muna (Lentera Perawat, 2025)
Background Burnout among healthcare workers, especially nurses, is a growing concern globally, driven by emotional strain, limited autonomy, and organizational challenges. While quantitative studies have identified burnout prevalence, little is known about how nurses in Oman experience and interpret the causes of burnout in their work environments. Objective This study aimed to explore the contributing factors to burnout among nurses in public healthcare facilities in Oman and to gain a deeper understanding of their lived experiences within the healthcare system. Methods A qualitative descriptive design was employed between October 2024 and February 2025. Ten nurses were purposively selected from public hospitals and primary healthcare centers across different regions in Oman. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis. Lincoln and Guba’s criteria were applied to ensure trustworthiness. Results Two main themes emerged: (1) emotional and physical burden of undervaluation and its impact on professional satisfaction, and (2) constraints on autonomy and opportunities for empowerment. Nurses reported experiences of fatigue, lack of recognition, restricted decision-making power, inequitable access to training, and marginalization in interdisciplinary settings. Conclusion Burnout among nurses in Oman is shaped by emotional exhaustion, limited autonomy, and systemic inequities. These findings underscore the need for institutional reforms that promote professional recognition, expand development opportunities, and foster supportive workplace cultures. Addressing these challenges is crucial for sustaining the nursing workforce and enhancing care quality.